Effect of a monitored home-based exercise program combined with a behavior change intervention and a smartphone app on walking distances and quality of life in adults with peripheral arterial disease: the WalkingPad randomized clinical trial - Ivone Silva; Ivone Silva; Ivone Silva; Célia Sofia Moreira; Susana Pedras; Rafaela Oliveira; Carlos Veiga; Luís Moreira; Daniel Santarém; Daniel Guedes; Hugo Paredes; Hugo Paredes (Frontiers in Cardiovascular Medicine, 2023)
AimsInvestigate whether a Home-based Exercise Therapy (HBET) program for patients with Peripheral Arterial Disease (PAD) and Intermittent Claudication (IC) with a behavior change intervention, supported by a smartphone application, is effective in improving walking distances and performance, and quality of life (QoL) over 6 months.Methods and resultsThis was a single-center, prospective, two-arm, single-blinded randomized controlled trial including 73 patients with PAD and IC, and three assessment moments: baseline, 3, and 6 months. Participants were randomized to receive a walking exercise prescription, with the support (n = 38) or without the support (n = 35) of the WalkingPad app, between January 2021 and July 2022. Both groups received two face-to-face behavior change sessions and 12 structured and targeted reinforcement phone calls over 6 months. Primary outcomes were between-group differences in pain-free walking distance (PFWD), functional walking distance (FWD), maximal walking distance (MWD), and 6-min walk distance (6 MWD) at 3 and 6 months. Secondary outcomes were QoL and walking impairment. Seventy-three patients (mean age 64 ± 7.2 years, 88% men) participated in this study, 60 of whom completed the three assessment moments. The whole sample significantly improved all primary outcomes in the first 3 months; that is, the average PFWD (151.1 m), FWD (175.2 m), MWD (171.1 m), and 6 MWD (30.8 m) increased from T1 to T2. Only MWD exhibited a significant average increase (35.0 m). Secondary outcomes also increased from baseline to 3 and 6 months. There were no between-group differences, except for MWD, which showed a greater increase at 6 months in the group that used the app, excluding patients with weak walking ability and extreme anxiety symptoms at baseline.ConclusionThe intervention improved distances and walking skills as well as the physical, mental, and disease-related quality of life among adults with PAD and IC. The group that used the WalkingPad app improved their MWD in 6 months compared to the control group, except for patients with poor walking ability and extreme anxiety symptoms, which suggests the effectiveness of the WalkingPad app for patients with high walking ability and no severe anxiety symptoms. More research is needed to determine the durability of these findings and to explore what app functionality might promote the other outcomes. Clinical Trial Registrationhttps://clinicaltrials.gov (NCT04749732).